EFEKTIVITAS PENGGUNAAN LKPD UNTUK MENINGKATKAN LITERASI NUMERASI PESERTA DIDIK - Miralda, Dara; Marhaeni, Nafida Hetty (TRANSFORMASI, 2023)
The aim of this research is to determine the effectiveness of using LKPD in increasing the literacy and numeracy of class VIII students of SMP Negeri 4 Yogyakarta. The material contained in the LKPD is the System of Linear Equations in Two Variables (SPLDV). This research is an experimental type with a pretest-posttes control group design. The results show that the use of LKPD is effective in increasing literacy-numeracy compared to learning without using LKPD. This is supported by the Wilcoxon test which show the Asymp. Sig. (2-tailed) of 0.000 which is less than 0.050, meaning that there is an increase in literacy-numeracy in the control class after implementing learning without using LKPD. Apart from that, the results of the Mann-Whitney test also show that the Asymp. Sig. (2-tailed) is 0.039 which is less than 0.050, meaning that learning using LKPD is more effective than learning without using LKPD. The average test results show that the average increase in the experimental class the average control class . Based on these results, it can be recommended to use LKPD to increase the literacy-numeracy of students at SMP Negeri 4 Yogyakarta.